2014
DOI: 10.1159/000360770
|View full text |Cite
|
Sign up to set email alerts
|

Is Chronic Obstructive Pulmonary Disease a Disease of Aging?

Abstract: Chronic obstructive pulmonary disease (COPD) is a disease that usually presents clinically at an advanced age, after years of smoking cigarettes. It is usually believed that aging and its biological consequences are important mechanisms in the disease pathogenesis. This concept has maintained the focus of studies on COPD in old-age individuals. Here we analyze the possible role of aging from a different point of view and introduce different concepts that might be considered useful additions to the understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…In the present study, it was observed that 36% of newly diagnosed patients were already Stage II and 26% Stage III, which is supported by previous studies [36]. It could be strongly argued that, due to the production of constant stresses that induce cell damage and eventual senescence, COPD might be directly responsible for accelerated aging, with all its untoward effects, rather than being a consequence of aging [37].…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, it was observed that 36% of newly diagnosed patients were already Stage II and 26% Stage III, which is supported by previous studies [36]. It could be strongly argued that, due to the production of constant stresses that induce cell damage and eventual senescence, COPD might be directly responsible for accelerated aging, with all its untoward effects, rather than being a consequence of aging [37].…”
Section: Discussionsupporting
confidence: 88%
“…A recent hypothesis suggested that these two entities share common pathogenetic mechanisms of accelerated senescence via telomere length abnormalities [11]; moreover, we must consider that the life expectancy has gone up, thus allowing more time for a chronic indolent progressive disease to manifest itself [12]. Not surprisingly, cases of simultaneous emphysema and pulmonary fibrosis have been finally described and proposed as a distinct entity termed combined pulmonary fibrosis and emphysema [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Lung injury, due to chronic oxidant exposure to CS, leads to cellular damage, the disruption of alveolar maintenance, and increased expression of markers of cellular senescence. Ito et al , therefore, first proposed that COPD was a disease due to accelerated aging of the lung 45 , and others have supported this hypothesis 15, 46, 47 . Although age does not affect the development of emphysema and small airway remodeling 48 , Cosio et al later refined the aging hypothesis and proposed that COPD is a disease of young susceptible smokers that progresses over time, accelerating lung damage, and then manifesting itself later in life 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Ito et al , therefore, first proposed that COPD was a disease due to accelerated aging of the lung 45 , and others have supported this hypothesis 15, 46, 47 . Although age does not affect the development of emphysema and small airway remodeling 48 , Cosio et al later refined the aging hypothesis and proposed that COPD is a disease of young susceptible smokers that progresses over time, accelerating lung damage, and then manifesting itself later in life 47 . Consequently, the molecular mechanism of accelerated aging can provide several therapeutic targets for novel intervention strategies against COPD 16, 49 .…”
Section: Discussionmentioning
confidence: 99%